Viral Hepatitis in Pakistan; a global concern - Ishaq, Muhammad Uzair; Rasheed, Faisal (Journal of the Pakistan Medical Association, 2024)
Dear Mam, Around 1.4 million people die each year from problems connected to hepatitis, with HBV infection accounting for the majority of cases and HCV infection coming in second1. Infection with HCV and HBV can range in severity from a mild illness with viral clearance to chronic hepatitis C that may lead to liver failure and death. There are an estimated 411,000 annual HCV-attributable deaths globally, with most of these resulting from liver cirrhosis or hepatocellular carcinoma that can manifest decades after infection2. According to the WHO report, hepatitis is the eighth highest cause of mortality. Pakistan bears the second-largest burden of hepatitis C globally, with a nationwide prevalence of 4.8% 1.A review of ninety different studies conducted in Pakistan observed that the prevalence of HCV infection in the adult population of Pakistan was 11.55%. Drug users were found to have the highest prevalence of 51%. The percentage prevalence of HCV found for all of the provinces was Punjab: 5.46%, Sindh: 2.55%, Khyber Pakhtunkhwa: 6.07%, Baluchistan: 25.77%, and federally administrated tribal areas: 3.37%. The study further observed that the average prevalence of viral hepatitis in Pakistan was a whopping 8.64%1. The main risk factors for transmission of viral hepatitis in Pakistan are unprotected sexual contact, quackery, use of unsterilized instruments in neighbourhood barber shops and shortage of designated maternity and obstetric centers3. People in Pakistan receive an unusually high number of therapeutic injections, estimated at between 4-5 injections a person per annum. An estimated 17 to 50% of these are given with previously used syringes2. It is high time our healthcare authorities, hospital administrators, health ministries and policy makers start making a comprehensive plan to curb viral hepatitis transmission in Pakistan. As for primary prevention, awareness campaigns should be organized, quackery be stopped, barbers trained in prevention of blood-borne pathogens transmission and barber shops regularized and registered. For secondary prevention, nation-wide screening campaigns should be organized with a focus on High-prevalence areas such as Baluchistan, antiviral drugs be made in the country, economical provision of antiviral drugs to the masses, provision of rapid diagnostic kits to the hospitals and designated hepatitis centres should be established in each district. The healthcare commissions should make Task-forces to curb quackery and lodge police reports against those involved in it. Together, we can make a healthy Pakistan!